Nanotechnological Plastic Flooring: Implications for Broiler Chicken Performance, Health, and Carcass Quality - Bruna Barreto Przybulinski; Rodrigo Garófallo Garcia; Maria Fernanda de Castro Burbarelli; Irenilza de Alencar Naas; Claudia Marie Komiyama; Fabiana Ribeiro Caldara; Vivian Aparecida Rios de Castilho Heiss; Kelly Mari Pires de Oliveira; Renata Pires de Araújo; Jean Kaique Valentim (Veterinary Sciences)
This study evaluated the effects of two types of plastic flooring—one with and one without nanotechnological antimicrobial additives—used as complete or partial replacements for wood shavings on broiler chicken performance, yield, meat quality, and litter microbiology over 42 days. A total of 1500 Ross 408® male broiler chicks were randomly assigned to five treatment groups: wood shavings (WS), plastic flooring (PF), a 50/50 mix of plastic flooring and wood shavings (PF + WS), plastic flooring with antimicrobial additives (PFA), and a 50/50 mix of antimicrobial plastic flooring and wood shavings (PFA + WS). This study evaluated organ biometrics (liver, heart, spleen, and gizzard), the severity of Eimeria lesions, microbiological profiles, performance indices, and meat quality. The results indicated that plastic flooring, particularly when used alone, presented challenges such as increased intestinal lesions related to coccidiosis and a higher prevalence of Salmonella. Moreover, broilers raised on plastic flooring presented worse feed conversion and lower body weights and carcass yields than those raised on wood shavings. The meat quality was also negatively affected, with plastic flooring leading to less favorable fillet characteristics. Overall, the use of plastic flooring reduced the performance and health parameters of broiler chickens.